Two-sided platforms: Dynamic pricing and multiple equilibria - Przemyslaw Rys; Maciej Sobolewski (European Commission, Joint Research Centre (JRC), 2020)
The static model of two sided markets proposed by Rochet and Tirole analyses optimal pricing of a monopolistic platform at the equilibrium point. Their framework implicitly assumes that for each prices set by the platform, the equilibrium number of users on each side will be unique. However, under general conditions, the uniqueness of market equilibrium is not guaranteed. Optimal static prices do not ensure convergence to the preferred full market outcome, as platform may face failure-to-launch or failure-to-grow problems. Hence, to study problems around multiplicity of equilibria, a different framework is required. We propose a dynamic model of monopolistic platform and demonstrate the effects of different dynamic pricing strategies for equilibrium selection and convergence. The main conclusion from the study is that emerging platform can reach the preferred equilibrium by using tariffs with subsidies for early stage users. We give examples of dynamically adjusting tariffs that minimize subsidies. Finally, the dynamic setting reveals a trade-off between the platform profits and social welfare, related to the speed of user base growth.
Keywords: C61; D42; L12; 330; two-sided markets; dynamic pricing; multiplicity of equilibria; dynamic system; online platforms